Infrastructure and cluster development: A case study of handloom weavers in Ethiopia - Ayele, Gezahegn; Chamberlin, Jordan; Moorman, Lisa; Wamisho, Kassu; Zhang, Xiaobo (International Food Policy Research Institute, 2009)
Rural non-farm development plays a key role in generating employment in many developing countries. Clustering is an important industrial organization in the rural non-farm sector. Based on primary surveys of both urban and rural handloom weaver clusters in Ethiopia which took place in May/June 2008, one of the most important rural nonfarm sectors, this paper examines the mechanism and performance of clustering. The clustering way of handloom production is observed even in remote rural areas, illustrating its vitality and flexibility in adapting to restricted environments. Despite its resilience in surviving in harsh environments, improvements in infrastructure can significantly increase labor productivity in a cluster. In towns with electricity access, producers work longer hours than those in towns without electricity and more entrepreneurs with limited access to capital are able to participate in handloom production because of finer division of labor.